ANALISIS MODEL PEMBELAJARAN PjBL BERBASIS HOTS PADA KEMAMPUAN KOLABORATIF PESERTA DIDIK KELAS V SD NEGERI LAWEYAN SURAKARTA TAHUN PELAJARAN 2024/2025: Penelitian Deskriptif - fradita mulawanah, chika; Handini, Oktiana; Hastini, Dite (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to analyze and describe the implementation of the HOTS-based Project-Based Learning (PjBL) model and its impact on the collaborative skills of fifth-grade students at SD Negeri Laweyan Surakarta. This research was conducted at SD Negeri Laweyan Surakarta. The subjects of this study were 28 fifth-grade students, the fifth-grade teacher, and the principal of SD Negeri Laweyan Surakarta. This study employed a qualitative approach with data collection techniques including observation, interviews, and documentation. Data collection utilized source triangulation and technique triangulation. The data were analyzed using a cyclical model comprising data reduction, data display, and conclusion drawing or verification. Based on the data analysis, the study concludes the following: (1) The HOTS-based PjBL model effectively enhances students’ collaborative abilities by actively involving them in problem formulation, solution design, and completing projects together in groups; (2) The HOTS-based PjBL model effectively develops students’ critical thinking skills through project-based learning activities that emphasize analysis, evaluation, and creation; and (3) The HOTS-based PjBL model significantly improves students’ communication skills through project-based learning activities that require in-depth analysis, group discussions, and presentations of their work.